Desafios da participação das mulheres no sindicalismo rural no território Chapada Diamantina: elaboração de guia orientador com foco nas políticas públicas e no trabalho feminino. - Santos, Cristiane Nascimento (2018)
In order to treat gender issues in rural areas and the implications of these discussions, we present the concept of gender, the ruling of the struggle movement and the achievements of women in the trade union movement, the generational succession and the sexual division of labor. The process of product intervention and elaboration that we have had as general objective the elaboration of a guideline related to the gender issues in rural areas, with focus on the leading role of the women leaderships of Rural Workers' Unions within the municipalities that make up the Chapada Diamantina Identity Territory. Thus, by identifying the profile of women union leaders, it was possible to observe that they are mostly young women, divide the domestic activities with another member in the residence, and some of them had access to higher education. In the preparation of the Guidance guide, from the realization of three workshops with women, using a participatory methodology, it was possible to construct a product that brings the themes of Public Policies for Women and the Sexual Division of Labor from their vision and what they considered important is present